Trees as Experts in Site-Specificity - Arlander, Annette (Routledge, 2024)
Experiences of performing for the camera with pine trees form the basis for this text, which focuses on performances conducted on Örö Island in southwestern Finland in 2021. An exploration of the pine trees’ specific relationship to that site through site-based movement practice of posing with the pines for a video camera on a tripod began with the understanding that plants, including trees, are extremely sensitive to their surroundings. They reflect in their form and growth their relationship to the specific environment while simultaneously also producing that environment. After presenting some philosophical ideas about plants’ relationship to site, I introduce the context for these explorations and look at some strategies for performing for camera with pine trees, especially experiments with a double perspective on the same site. I suggest that a visual approach can highlight different aspects of a site and focus on other than human performers like pine trees.
Keywords: paikkasidonnainen taide; performanssi; puut (kasvit); vuorovaikutus; esittävät taiteet; taiteellinen työ; Örö (Kemiönsaari); taiteellinen tutkimus